First Report on Nitrogen’s Role in Vivipary Suppression in Late-Maturing Mango cv. Sufaid Chaunsa (Journal of Agriculture and Biology, 2025)
Punjab is the major mango producing region in Pakistan whereas Pakistan is fifth in the globe in mango production. Among the late season varieties with an 18 % share in Punjab’s mango area, the premium Sufaid Chaunsa variety has an exponential share of export but suffers postharvest losses due to a disorder known as vivipary, which causes seeds to germinate too early. The objective of this study was to assess the influence of different doses of nitrogen supplied at flowering and fruit setting stages on vivipary incidence in Sufaid Chaunsa. Experiment was conducted under randomized complete block design with four nitrogen treatments (0 g, 200 g, 300 g, and 500 g per tree), and three replications. Data were collected when fruit get ripened after fruit harvest. Results showed that with an increase in the nitrogen doses manifested an increase in the vivipary expression. In the case of 500 g nitrogen treatment (T₃), the percentage of viviparous seeds (100%) and pulp vivipary (45.45%) was the highest while the lowest among all were in control (T₀ - 65.15% and 1.51%, respectively). Antioxidant capacities and phenolic contents increased with higher nitrogen application, and root length of germinating seed (vivipary) increased as well, which indexing a more general correlation between nitrogen induced metabolic changes and vivipary expression. Vivipary in mango, as of now, is reported for the first time, focusing on the mechanism of the phenomenon and its practice in late maturing varieties. These findings indicate that nitrogen management strategies to reduce vivipary while maintaining fruit quality are needed in mangoes. Research on the effects of growth regulators and irrigation practices on vivipary suppression is also recommended.